(untitled) (Faridpur Medical College Journal, 2014)
This case control study was conducted in the department of Gynae & Obstetrics, Sir Salimullah Medical College & Mitford Hospital (SSMC & MH), Dhaka, during the period of January 2008 to December 2008 to compare the length of operation, blood loss, length of hospital stay, drug requirements for pain and post-operative pain and activity levels between Laparoscopically Assisted Vaginal Hysterectomy (LAVH) & Total Abdominal Hysterectomy (TAH). A total of 50 patients who met some eligibility criteria were consecutively included in the study and matched in a case control manner for age, weight, diagnosis & uterine size. The procedures were performed by the same surgeon. On average, LAVH operations took significantly longer than TAH operations (P<0.001). Equal number of patients of both groups (40%) needed blood transfusion. No significant difference about haemoglobin level compared to TAH group on 3rd POD (P=0.246). However total amount of analgesics needed was much higher in the TAH group than that of the LAVH group (243.7 ± 40.3VS 182.1 ± 69.6 mg; P= 0.005) and the total cost of operation was significantly less in the TAH group (4500 ± 500 takas) than in the LAVH group (6500 ± 500 taka) (P<0.001). It was observed that LAVH group produced earlier relief from pain in terms of pain VAS on 3rd POD, (P<0.001). LAVH is less painful, has a shorter length of hospital stay and quicker return to work than TAH. Moreover LAVH does not increase intra or postoperative complications. DOI: http://dx.doi.org/10.3329/fmcj.v8i2.20370 Faridpur Med. Coll. J. 2013;8(2): 59-62